2006
DOI: 10.1111/j.1365-2842.2006.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implant support on distal extension removable partial dentures: in vitro assessment

Abstract: The implants in implant-supported removable partial dentures (RPDs) are placed in the edentulous ridge to stabilize the RPD and minimize the resultant rotational movement. This study investigated the effect of implant placement on RPD stability. A model simulating a mandibular bilateral distal extension missing was fabricated using epoxy resin and silicone impression material as thin (1 mm) and thick (2 mm) soft tissues. Five pressure sensors (PS-10K, Kyowa, Tokyo, Japan) were attached near the left and right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
1
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(202 citation statements)
references
References 18 publications
(25 reference statements)
9
173
1
19
Order By: Relevance
“…There is an absence of contrasted, and more long-term, evidence on the reduction or non-overloading of implant angulation, following the All on four protocols [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an absence of contrasted, and more long-term, evidence on the reduction or non-overloading of implant angulation, following the All on four protocols [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated and is a biomechanical principle that the overall stress on the entire implant / peri-implant bone system is reduced by increasing the area on which the force is applied and the most effective method to achieve this is to increase the number of implant supports prosthesis. In general, although the number of implants may vary depending on the type of prosthetic restoration, other parameters such as factors of patient strength, quantity and bone quality, prosthetic space, nature 21 Patients with five years of use or without follow-up data in nine patients [5]. Even in a recent in vitro study it was shown that in both prostheses retained by one or two implants, lateral forces on the abutments were similar.…”
Section: Number and Distribution Of Implantsmentioning
confidence: 99%
“…Implants can be placed in the distalextension-areas for resolving these problems. [18][19][20][21][22][23][24][25][26] Patients and most clinicians generally prefer fixed prostheses. However, there are some situations in which IRRPDs may be considered as the only possible treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…So that there is no need to sinus augmentation or nerve-repositioning-surgery, 10) Converting a Kennedy Class Ι or II RPD to a toothimplant-supported RPD which may be considered as a Kennedy Class III, 11) Psychological benefit of preserving patient's natural teeth with less than optimal prognosis, at least for an interim period, 12) A "staged" approach in implant insertion may be performed according to patient's budget, 3,14,18,20,[26][27][28][29][30] 13) Oral hygiene may be provided more easily than fixed prostheses and nocturnal bruxism can be reduced or eliminated due to its removal during night, 12,31 14) In the case of greater crown-height-space (CHS) resulting from excessive RRR, macrotrauma or ablative surgery, IRRPD seems to be a better biomechanical option. …”
Section: Discussionmentioning
confidence: 99%
“…And attachment can be connected to implant for retention and support in implant retained partial overdenture (IR-POD). 5,6 Although several retrospective ISRPD studies have shown a high survival rate of implant, some mechanical complications can occur. de Freitas et al 7 reported that ISRPD had a high success rate ranging from 95 -100% and good patient's satisfaction but showed several complications such as pitting of the healing abutment, replacement of resilient component of the attachment, damage in framework, screw loosening and damage in acrylic denture base.…”
Section: Introductionmentioning
confidence: 99%